MANIFESTATION OF STUDENTS’ INDEPENDENT ACTIVITY AT UNIVERSITY (CASE OF STUDENTS IN SOCIAL SCIENCE) - Rutkienė, Aušra; Tandzegolskienė, Ilona (Acta Paedagogica Vilnensia, 2013)
The main function of higher education institutions is to prepare students for their future activity, to develop their creative strengths, critical thinking, problem solving and constructive communication skills. One of the most important abilities of an active, responsible individual who can act independently is self-management, i.e. being able to plan and organise one’s learning process and ability to reflect. A university research has revealed that some 1st -year and 4th -year social science students describe learning independence as student’s participation in planning, monitoring, correcting, and assessing one’s own learning process and results. The emphasis is put on creativity, ability to make right decisions in a new learning situation when putting the present and new knowledge together, search for more diverse solutions, taking responsibility for the learning process and future outcomes.